Surfactin secreted by Bacillus amyloliquefaciens Ba01 is required to combat Streptomyces scabies causing potato common scab - Feng, Ru-Ying; Chen, Yi-Hsuan; Lin, Chih; Tsai, Chia-Hsin; Yang, Yu-Liang; Chen, Ying-Lien (Frontiers in Plant Science, 2022)
Potato common scab, which is mainly caused by the bacterium Streptomyces scabies, occurs in key potato growing regions worldwide. It causes necrotic or corky symptoms on potato tubers and decreases the economic value of potato. At present, there is no recommended chemical or biological control for combating potato common scab in Taiwan. It can only reduce the occurrence by cultivation control, but the efficacy is limited. Previously we found that Bacillus amyloliquefaciens Ba01 could control potato common scab in pot assay and in the field. The potential anti-S. scabies mechanism was associated with surfactin secretion, but further molecular dissection was not conducted. Thus, in this study we aimed to determine whether surfactin is the main compound active against S. scabies by knocking out the srf gene cluster in Ba01. The cloning plasmid pRY1 was transformed to Ba01 by electroporation for in-frame deletion. Two independent Δsrf mutants were obtained and confirmed by specific primers and mass spectrometry. The swarming ability and S. scabies inhibition was significantly decreased (P<0.001) in Δsrf mutants. The swarming ability of Δsrf mutants could be restored by the addition of surfactin. Furthermore, we found that Ba01 formed wrinkled biofilm in MSgg liquid medium, while Δsrf mutants formed biofilm abnormally. Furthermore, the α-amylase, protease and phosphate-solubilizing ability of Δsrf mutants was decreased, and the mutants could not inhibit the growth and sporulation of S. scabies on potato tuber slices. In conclusion, srf gene cluster of B. amyloliquefaciens Ba01 is responsible for the secretion of surfactin and inhibition of S. scabies.